If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5a + 1)(2a + 7) = 0 Reorder the terms: (1 + 5a)(2a + 7) = 0 Reorder the terms: (1 + 5a)(7 + 2a) = 0 Multiply (1 + 5a) * (7 + 2a) (1(7 + 2a) + 5a * (7 + 2a)) = 0 ((7 * 1 + 2a * 1) + 5a * (7 + 2a)) = 0 ((7 + 2a) + 5a * (7 + 2a)) = 0 (7 + 2a + (7 * 5a + 2a * 5a)) = 0 (7 + 2a + (35a + 10a2)) = 0 Combine like terms: 2a + 35a = 37a (7 + 37a + 10a2) = 0 Solving 7 + 37a + 10a2 = 0 Solving for variable 'a'. Factor a trinomial. (7 + 2a)(1 + 5a) = 0Subproblem 1
Set the factor '(7 + 2a)' equal to zero and attempt to solve: Simplifying 7 + 2a = 0 Solving 7 + 2a = 0 Move all terms containing a to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 2a = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 2a = 0 + -7 2a = 0 + -7 Combine like terms: 0 + -7 = -7 2a = -7 Divide each side by '2'. a = -3.5 Simplifying a = -3.5Subproblem 2
Set the factor '(1 + 5a)' equal to zero and attempt to solve: Simplifying 1 + 5a = 0 Solving 1 + 5a = 0 Move all terms containing a to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 5a = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 5a = 0 + -1 5a = 0 + -1 Combine like terms: 0 + -1 = -1 5a = -1 Divide each side by '5'. a = -0.2 Simplifying a = -0.2Solution
a = {-3.5, -0.2}
| 39-3x-3=7x | | 6x^2+x-6=0 | | 8x^3+10x-3=0 | | 2x+3x-5y-3y= | | -3z-4=10 | | -x=8y+5 | | log(w)=3 | | ln(w)=3 | | 28+6n=-7(3+5n)-8n | | 9x-8=6x+3 | | -3(2x-y)=0 | | -40-8v=-8(2v+3) | | (m+7)(m+5)= | | x^2+y^2-4x+6y=13 | | -b-2=78 | | a-2b=-5 | | c^2-4x-21=0 | | 34-x=-3(2x+2) | | (6g-2)+8(1-5g)=2g | | log[2](9x+8)=2 | | 2m+4-8m=-28 | | 5(17c+4)= | | 2x-tan(x)=0 | | -3x+6+7y=5 | | B-9+6p=30 | | 18=4+31t-16t^2 | | 3s(3)=5+s(4) | | (9a^2+2)(9a^2+a+1)= | | -20+7x=-6+8(2x+5) | | 5x=2x+10+10+7 | | 14c-9c=10 | | -5m-5m=14-3m |